Tecnologia em nuvem aplicada a Internet das Coisas - Franco, Cleverson Ferreira (2018)
The cloud has long been used to host web applications in recent years for its security, speed, and reliability. With the growing Internet wave of Things coming up, it is necessary to evolve with technology in the infrastructure layer, and web technology, so that an IoT application has a complete ecosystem. The study aimed to build the web part of a secure, high performance, monitored and high availability application using new technologies in both the structural part using queuing system, cloud hosting, realtime monitoring, and in the part of code, where PHP was used, one of the most used programming languages in the world. The result achieved reached the expected goals, as it resulted in a simple, organized, easy-to-manage platform, and adaptable to new improvements and future implementations.